USE OF INTERACTIVE TEACHING METHODS IN THE FORMATION OF STUDENTS’ CREATIVE ABILITIES - Abdukadirova Shakhnoza Gafurovna; Akhrarova Nigora Sabirovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article describes the concept of creativity, interactive methods, interactive teaching methods and technologies, an interactive educational process aimed at developing creative abilities, pedagogical conditions, practical development and improvement of cognitive knowledge, the formation of students’ creative abilities.